Features of Development and Manifestation of Emotional Burnout Syndrome in Pediatricians - О.K. Koloskova; M.I. Polishchuk; T.M. Vorotnyak (Zaslavsky O.Yu., 2012)
We studied the features of the development and manifestations of emotional burnout syndrome in 30 pediatricians of different specialties. It is noted that the syndrome of emotional burnout in pediatricians goes through three phases: in phase of stress it is characterized primarily by excessive experience of stressful circumstances, in phase of resistance manifests with economy of the emotional sphere, in phase of exhaustion - with emotional deficit. It was shown that in pediatricians the features of the manifestations of emotional burnout syndrome depending on the specialty were not revealed, but in male doctors emotional burnout more often develops on the basis of the symptoms of dissatisfaction, emotional deficit and depersonalization.